Transcriptome-Wide N6-Methyladenosine (m6A) Profiling of Susceptible and Resistant Wheat Varieties Reveals the Involvement of Variety-Specific m6A Modification Involved in Virus-Host Interaction Pathways - Zhang, Tian-ye; Wang, Zi-qiong; Hu, Hai-chao; Chen, Zhi-qing; Liu, Peng; Gao, Shi-qi; Zhang, Fan; He, Long; Jin, Peng; Xu, Miao-ze; Chen, Jian-ping; Yang, Jian (Frontiers in Microbiology, 2021)
N6-methyladenosine (m6A) methylation is the most prevalent internal modification of post-transcriptional modifications in mRNA, tRNA, miRNA, and long non-coding RNA in eukaryotes. m6A methylation has been proven to be involved in plant resistance to pathogens. However, there are no reports on wheat (Triticum aestivum) m6A transcriptome-wide map and its potential biological function in wheat resistance to wheat yellow mosaic virus (WYMV). To the best of our knowledge, this study is the first to determine the transcriptome-wide m6A profile of two wheat varieties with different resistances to WYMV. By analyzing m6A sequencing (m6A-seq) data, we identified 25,752 common m6A peaks and 30,582 common m6A genes in two groups (WRV and WSV), and all these peaks were mainly enriched in 3ʹ untranslated regions and stop codons of coding sequences. Gene Ontology analysis of m6A-seq and RNA-seq data revealed that genes that showed significant changes in both m6A and mRNA levels were associated with plant defense responses. Kyoto Encyclopedia of Genes and Genomes analysis revealed that these selected genes were enriched in the plant–pathogen interaction pathway. We further verified these changes in m6A and mRNA levels through gene-specific m6A RT-qPCR and normal RT-qPCR. This study highlights the role of m6A methylation in wheat resistance to WYMV, providing a solid basis for the potential functional role of m6A RNA methylation in wheat resistance to infection by RNA viruses.